2021
DOI: 10.1088/1755-1315/665/1/012069
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and coastal vulnerability assessment methods: A review

Abstract: Coastal and marine ecosystems have been threatened at local and global scales by multiple stressors – sea-level rise, rising temperatures, climate extreme events, biodiversity loss and habitat destruction. These stressors operating independently or synergistically could alter the ecosystem services while posing a significant threat to the environment, human lives and properties, as well as, result in biophysical and socio-economic losses. In this paper, we present an overview of the methods used in assessing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These are the Barrier-lagoon coastal complex, the Mahin transgressive mud coast, the arcuate delta, and the Strand coast [15]. The coastline zones were divided into seventeen (17) segments (as shown in Figure 1) across the geomorphic units along the coast bordering the equatorial Atlantic Ocean and the individual vulnerability variables were designated respective rank or number ranging from 1 to 5, such that 5 and 1 indicated the highest and lowest vulnerabilities, respectively. The coastal vulnerability rankings used in this study are shown in Table 1.…”
Section: Methodology and Study Area 21 Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…These are the Barrier-lagoon coastal complex, the Mahin transgressive mud coast, the arcuate delta, and the Strand coast [15]. The coastline zones were divided into seventeen (17) segments (as shown in Figure 1) across the geomorphic units along the coast bordering the equatorial Atlantic Ocean and the individual vulnerability variables were designated respective rank or number ranging from 1 to 5, such that 5 and 1 indicated the highest and lowest vulnerabilities, respectively. The coastal vulnerability rankings used in this study are shown in Table 1.…”
Section: Methodology and Study Area 21 Study Areamentioning
confidence: 99%
“…The coastline is low-lying [16], and it is endowed with a vulnerable mangrove system, which has depleted over time due to anthropogenic activities such as crude oil exploration, use of wood as fuel, timber, fishing, sand mining, etc. [17]. Lack of government policies that protect these vital ecosystems has contributed enormously to its destruction.…”
Section: Introductionmentioning
confidence: 99%